PATTERNS OF FUNCTIONING OF THE FAMILY OF ORIGIN AND THE EMOTIONAL INTELLIGENCE OF YOUNG ADULTS - KOROL, EWA (Studia Psychologica: Theoria et praxis, 2015)
This article describes the research concerning the connection between the level of general emotional intelligence, and its individual components, among young adults and the model of functioning of their family background. The analysis was conducted on the sample of 121 individuals, 72 women and 49 men, aged 21-26. Within the context of this work a family is understood in accordance with a systemic perspective and EI in accordance with the ability model. The following methods have been used in the study: Polish adaptation FACES-IV (Flexibility and Cohesion Evaluation Scales) David H. Olson’s, Popular Questionnaire of Emotional Intelligence and own survey. The article contains the discussion of the results, which shows that there is a statistically significant relation between the specific model of family background of young adults and their general level of EI with its individual abilities.